Descrição e análise dos culturemas do português brasileiro - Pinheiro, Michelle Girão (2018)
This research aims to investigate the Brazilian Portuguese (BP) culturemes. We collected these cultural components in Brazilian scientific papers with the intention of inventorying them according to the theoretical orientation of Luque Nadal (2009) and Pamies Bertrán (2008). According to Pamies Bertran (2007), culturemes are culturally motivated extralinguistic symbols, which are the basis for the different languages to generate new phraseological units. The survey of these extralinguistic symbols of BP will show us, besides a significant part of the cultural mirror of Brazil through the lexicon, the terminological fluctuation of the category exploited in our work. The description and categorization of these elements will therefore present the linguistic reflex of the phenomenon. Based on the theoretical bases of Lexiculture and Phraseology, we also intend to problematize the theoretical and methodological implications of this alliance. If the historical and cultural baggage of a society is inserted into the language by means of various phenomena, such as culturemes and phraseologisms, resulting in the impossibility of thinking the language disaggregated from these principles, then it is not boldness to defend this necessary relation, given the role played by culturemes, that is, to act as a vehicle for the transmission of culture of a people, and satisfactorily fulfill the function of enabling a transit between the two languages: mother tongue and foreign language. In addition, learning a foreign language contributes significantly to the development of communicative competence - the main objective of classes within a communicative approach. The relevance of our reflection is imposed insofar as it is admittedly sustainable that knowledge of a language goes beyond the domain of grammatical rules and lexical knowledge; in the last instance, the knowledge of cultural aspects, among which is the linguistic one.